Gene-specific targeting of the histone chaperone Asf1 to mediate silencing. - Goodfellow, H.; Krejci, A.; Moshkin, Y.; Verrijzer, C.P.; Karch, F.; Bray, S.J. (Developmental Cell, 2007)
The histone chaperone Asf1 assists in chromatin assembly and remodeling during replication, transcription activation, and gene silencing. However, it has been unclear to what extent Asf1 could be targeted to specific loci via interactions with sequence-specific DNA-binding proteins. Here, we show that Asf1 contributes to the repression of Notch target genes, as depletion of Asf1 in cells by RNAi causes derepression of the E(spl) Notch-inducible genes. Conversely, overexpression of Asf1 in vivo results in decreased expression of target genes and produces phenotypes that are strongly modified (enhanced and suppressed) by mutations affecting the Notch pathway, but not by mutations in other signaling pathways. Asf1 can be coprecipitated with the DNA-binding protein Su(H) and the corepressor Hairless and interacts directly with two components of this complex, Hairless and SKIP. Thus, in addition to playing more general roles in chromatin dynamics, Asf1 is directed via interactions with sequence-specific complexes to mediate silencing of specific target genes.